(untitled) (Fiep Bulletin - online, 2011)
This article is a reflexion regarding the role of physical education during the governance of Getulio vargas in Brazil. This activity was used as an instrument of control of the body, as well as a way to structure them, with the intention to reach physical perfection based in the racial purity principles. The government used public commemorative events for the application of these control mechanisms, lessening the population’s resistence to their ideals and developing the support of the population.